SENI TRADISIONAL DALAM SENI RUPA MODREN: ANALISIS BERDASARKAN NILAI PENDIDIKAN - Budiwirman Budiwirman; Syeilendra Syeilendra; Ary Ramadhan; Syafei Syafei (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Traditional arts that have high artistic value must always be preserved from extinction. In order to maintain the popularity of traditional art in Indonesia, it is necessary that artists, teachers, and society understand it deeply. Every fine arts artist, teacher, and community must have a sense of nationalism towards traditional art in order to be able to maintain and become a stronghold of traditional art itself. This study aims to rediscover the values of traditional culture that are spread in several regions in Indonesia with the hope that it can be absorbed into modern art so that the value of traditional art is not completely eroded. This research uses Spradley's qualitative research method or ethnographic qualitative research with the aim of systematically describing deeper cultural characteristics. This research produces a description of the characteristics of traditional culture contained in several traditional arts and crafts spread across Indonesia, each region has cultural characteristics that are different from other regions which are influenced by several diverse factors. The characteristics of each artistic value are maintained and absorbed into modern art for maintained and taught in the world of education so that art saviors are born who are able to transform traditional arts into modern artistic values. As art saviors, artists need awareness of a sense of